1999
DOI: 10.1074/jbc.274.36.25273
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Strain Stress-induced Mitogen-activated Protein Kinase (MAPK) Phosphatase 1 Expression in Vascular Smooth Muscle Cells Is Regulated by Ras/Rac-MAPK Pathways

Abstract: Recently, we demonstrated that mechanical stress results in rapid phosphorylation or activation of plateletderived growth factor receptors in vascular smooth muscle cells ( Intracellular signaling stimulated by growth factors, cytokines, osmotic shock, and stress involves the initiation of one or more phosphorylation cascades leading to the rapid and reversible activation of mitogen-activated protein kinases (MAPKs), 1 a family of ubiquitous and well characterized serine/threonine kinases thought to play a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
147
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(160 citation statements)
references
References 59 publications
9
147
2
Order By: Relevance
“…Platelet-derived growth factor receptor-␣ is activated in vascular SMCs in response to mechanical stretch in a ligand-independent fashion, leading to ERK2 activation and enhanced AP-1 binding activity (15). Using a general growth factor receptor inhibitor, Li et al (28) showed that ERK activation, but not p38 or JNK activation, was dependent on growth factor receptor activation in vascular SMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet-derived growth factor receptor-␣ is activated in vascular SMCs in response to mechanical stretch in a ligand-independent fashion, leading to ERK2 activation and enhanced AP-1 binding activity (15). Using a general growth factor receptor inhibitor, Li et al (28) showed that ERK activation, but not p38 or JNK activation, was dependent on growth factor receptor activation in vascular SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other cell types that employed in vitro stretch systems have demonstrated that cellular mechanotransduction activates multiple signaling molecules (41), including phospholipase C (PLC)-protein kinase C (PKC) (41), cAMP-protein kinase A (PKA) (8), the Janus kinasesignal transducers and activators of transcription (JAK-STAT) pathways (38), phosphatidylinositol 3-kinase (12), G proteins (13), small GTPases (1), receptor and nonreceptor tyrosine kinases (5,15,20,21,30), and, most notably, members of the mitogen-activated protein kinase (MAPK) family (24,28,42,44).…”
mentioning
confidence: 99%
“…In grafted veins, mechanical force on the vessel segment suddenly increases more than 10-fold (arterial versus venous blood pressure), which provides a strong stimulus to vascular endothelial and SMCs. 32 We previously demonstrated that acutely elevated blood pressure and mechanical stress activate growth factor receptor-MAPK signal pathways, [33][34][35][36] which are critical in mediating mechanical stress-induced cell apoptosis and proliferation. Hyperlipidemia may be an amplifying factor that exerts its effects on vein graft atherosclerosis in the presence of elevated biomechanical stress.…”
Section: Discussionmentioning
confidence: 99%
“…Much progress has been made in understanding the mechanical response of cardiovascular tissue where cells function in a dynamic system of pulsatile blood flow that creates shear, tension and pressure waves in expandable tubes at a rate of more than 60 times per minute (1 Hz, or 1 cps). Endothelial cells are known to respond to shear stress and cardiac myocytes to strain with teleologically understandable alterations (Li et al, 1999a;Wung et al, 1999). As well, the response of cells of the kidney (Hirakata et al, 1997;Ingram et al, 1999) and lung (Kulik and Alvarado, 1993), to name but a few other organs, demonstrably respond to their mechanical environments.…”
Section: Introductionmentioning
confidence: 99%